Penggunaan Sentimen Primordial oleh Pasangan Calon Joko Widodo-K.H. Ma’ruf Amin dan Prabowo Subianto-Sandiaga Salahuddin Uno di Provinsi Banten Pada Pemilu Presiden dan Wakil Presiden Tahun 2019 - Heri Handoko; Syahrul Hidayat (Syntax Corporation, 2023)
This study aims to identify and analyze the use of primordial sentiments in practical political aspects such as in the context of elections in Indonesia. The approach used in this study is a qualitative approach. A qualitative research approach is a process of research and understanding based on methodologies that investigate social phenomena and human problems. As a result, due to decentralization, the locus of political science studies began to pay more attention to aspects of ethnicity, regionality, sultanate and custom in political aspects. Second, the strengthening trend of using primordial symbols in tandem with the process of political liberalization manifested through multi-party political systems and direct electoral systems that tend to emphasize the principle of majority vote, thus making the use of primordial elements more fertile. In conclusion, as for the reality, the strengthening of the use of primordial sentiments in the context of politics is then considered to have made the political pattern tend to be primitive-traditional because some political figures and national and regional leaders tend to use primordial elements to achieve their respective political interests.